163k views
5 votes
Solve for x in this equation. 2(3x - 4) = 9(8 + 5x)

User Greg Motyl
by
5.2k points

2 Answers

6 votes

2(3x - 4) = 9(8 + 5x)

Mutiply the first bracket by 2

(2)(3x)(2)(-4)= 6x-8

Mutiply the second bracket by 9

(9)(8)(9)(5x)= 72+45x

6x-8= 72+45x

move -8 to the other side , sign becomes +8

6x-8+8= 72+8+45x

6x= 72+8+45x

6x= 80+45x

move +45x to the other side , sign becomes -45x

6x-45x= 80+45x-45x

6x-45x= 80

-39x= 80

divide both sides by -39

-39x/-39= 80/-39

x= -80/39 or x=-2 2/39

Answer: x= -80/39 or x=-2 2/39

User Joshua Warner
by
4.9k points
4 votes

Answer:


x=-80/39

Explanation:

We have the equation:


2(3x - 4) = 9(8 + 5x)

first we multiply 2 by (3x - 4) in the left side, and multiply 9 by (8 + 5x) in the right side:


6x-8=72+45x

now we move all terms with x to the left, and all independent terms to the right:


6x-45x=72+8\\-39x=80

finally we divide by (-39) both sides of the equation:


(-39x)/(-39)=(80)/(-39) \\x=-(80)/(39)

making this division we get:


x=-2.0513

or you can just leave the answer as
x=-80/39

User Sshturma
by
5.6k points